2024
DOI: 10.1186/s12887-024-04730-1
|View full text |Cite
|
Sign up to set email alerts
|

Chronic stridor in a toddler after ingestion of a discharged button battery: a case report

Zoe S. Oftring,
Doortje M. Mehrtens,
Julian Mollin
et al.

Abstract: Background Button battery (BB) ingestions (BBI) are increasingly prevalent in children and constitute a significant, potentially life-threatening health hazard, and thus a pediatric emergency. Ingested BBs are usually charged and can cause severe symptom within 2 h. Discharged BBs ingestion is very rare and protracted symptom trajectories complicate diagnosis. Timely imaging is all the more important. Discharged BBs pose specific hazards, such as impaction, and necessitate additional interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Common clinical presentations of BB impactions include vomiting, dysphagia, pain, drooling, cough, and fever, while rare manifestations may include unexplained crying, hoarseness, laryngeal stridor, dyspnea, and melena. Interestingly, some cases may present with no obvious discomfort [9] . Contrary to the European Society of Pediatric Button Battery Ingestion in Childhood guidelines [10] , which emphasize drooling and vomiting as major symptoms, our study found that vomiting and dysphagia were predominant complaints.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Common clinical presentations of BB impactions include vomiting, dysphagia, pain, drooling, cough, and fever, while rare manifestations may include unexplained crying, hoarseness, laryngeal stridor, dyspnea, and melena. Interestingly, some cases may present with no obvious discomfort [9] . Contrary to the European Society of Pediatric Button Battery Ingestion in Childhood guidelines [10] , which emphasize drooling and vomiting as major symptoms, our study found that vomiting and dysphagia were predominant complaints.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…Esophageal stenosis and perforation were the most common complications observed in our study, and tracheoesophageal stula should be considered when symptoms such as fever and cough occur after the operation. Fortunately, most children with complications can heal spontaneously without surgery [9,18,19] . Following the operation, patients were fed via gastric tube, and active anti-infection, acid inhibition, and symptomatic treatment were administered for a week.…”
Section: Clinical Characteristicsmentioning
confidence: 99%